(untitled) (Texas Journal of Philology, Culture and History, 2025)
This article examines the linguacultural features of somatic phraseological units (SPUs) in English and Uzbek. SPUs—idiomatic expressions involving body parts—reveal rich insights into cultural worldviews and shared human experiences. The study explores their formation, meanings, and functions, highlighting both universal and culture-specific elements. A contrastive analysis illustrates how SPUs encode values, emotions, and perceptions through somatic imagery in each language. The findings contribute to phraseological theory, intercultural communication, and language pedagogy